Bentuk Penyajian Kesenian Hadroh dalam Acara Selamatan Dimasa Pandemi oleh Kelompok Sabulussalam dalam di Kota Palembang - Rio Eka Putra; Sonia Anisah Utami (Departement of Mathematics Education, 2023)
Hadroh art is an art that combines the beats of several percussion instruments with rhythm or solawatan, with songs sung by religious poetry. The research aims to find out how the musical form of Hadroh music is in the salvation event during the pandemic by the Sabulussalam Dalam group in the city of Palembang. The problem is focused on the form of presentation, such as the form of wasps in several instruments, as well as the rhythms and songs that are presented. If observed from the style and rhythm, Hadroh is influenced by the Persian and Arabic culture that came to Palembang. The Arabic influence is very strong because the Sabulussalam group is close to an area in Palembang City with an Arabic village name. It can be seen from the form of tabuhan and solawatan poetry which is used as poetry and rhythm, while the elements of the rhythmic pattern and rhythm of the game are very clear in Ulu's style which is close to the river which has a strong impression and tight ties. In order to approach this problem, theoretical references are used. The research method is to choose a qualitative descriptive method, because this method makes it very easy for researchers to describe in the form of performances, then collect data through the stages (1) Observation, (2) Interview, (3) ) Documentation. And the stage of validity of the research data uses the member check method, as well as the stages of analyzing the research data including (1) Data Reduction, (2) Data Presentation, (3) Conclusion. This study concludes that it is found that every song in Hadroh music has a structural part, namely there is one period, two and three motives, and two phrases, namely question phrases and answer phrases, and has one sentence, where each structure is always repeated in the next part. it's just that the text of the song is different.